One community's secret - Ferraro, Joanne Marie (Acta Histriae, 2007)
For six years one small community of rustics working on a Venetian patrician's landed estate in the province of Padua kept a horrible secret: one of the field workers was fathering children with his daughter and then murdering them. A bounty hunter, hungry for a cash reward, turned the village gossip to his advantage, denouncing the affair to the Venetian Podesta, who set out to punish the "monstruous delinquents and abominable sinners" and restore Divine Law. This article analyzes the criminal inquiry, highlighting the testimonies of the accused, their neighbors, and their kin to reveal the ambiguities surrounding deviant behavior. The Venetian Podesta could not comprehend why no one, including the village priest, had denounced such obviously grave crimes to the state. Community members, on the other hand, were intent on keeping the incest and infanticide a secret because cohesion was more important to their collective livelihood and reputation than abuse and sin
Keywords: 16.st.; detomori; Galliera Veneta; incest; kulturna zgodovina; law; pravo; sodna praksa